Mechanical and Thermal Load Effect on Piston Crown of a Biogas Engine: A Simulation Approach - Nguyen The Truc; Tran Anh Duc; Nguyen Cam Van; Nguyen Khac Tung; Hoang Dinh Long; Trinh Xuan Phong; Khanh Nguyen Duc (Universitas Gadjah Mada, 2022)
This paper presents the study results on stress and deformation of the piston crown of a biogas engine converted from a conventional diesel engine using dedicated software. The original diesel engine was modified to reduce the compression ratio to suit biogas fuel. The original engine's combustion chamber and compression ratio were changed by modifying the piston crown to a heron type. The parameters of in-cylinder pressure and temperature were determined by the thermodynamic simulation software AVL Boost. Research results show that the in-cylinder pressure decreased compared to diesel when using biogas fuel, but the temperature increased. The infinite element method-based software was used to simulate the effects of mechanical and thermal load on stress and deformation on the piston crown of the biogas engine. As modeling with maximum pressure and temperature, the maximum stress on the piston crown was 3.425x109 N/m2 and 4.224x109 N/m2 for diesel and biogas. However, the maximum deformation in the biogas case was lesser than diesel, 0.3037 and 0.4186 mm. The minimum safety factor was 0.1012 and 0.0891 for diesel and biogas models, respectively.